Countzkey: Web Based Digital Learning Media Innovation For Special Journal Material For Grade XII Students at Senior High School 2 Bangkalan - Frizka Kinanti Ayyuza; Rochmawati Rochmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study developed a web based digital learning media COUNTZKEY for special journal material for class XII Economics at SMAN 2 Bangkalan, using a Research and Development (R&D) approach with the ADDIE model. Based on the phenomenon of minimal variation in conventional teaching media and the demands of digital learning for generation Z, this study aims to describe the development process, test the feasibility of material, media, and language aspects through expert validation, and analyze student responses. Subjects included two material experts, one media expert, one language expert, and 20 class XII IPS students. The instruments in the form of a Likert scale validation sheet and a Guttman scale response questionnaire were analyzed descriptively percentage. Expert validation produced an average of 88.7% or the